A prospective longitudinal cohort study for quality of life in patients undergoing fourth level liver surgery - Xu, Xiaofeng; Xu, Jing; Xu, Gang; Lv, Tao; Yang, Jiayin (Scientific reports, 2025)
Performing fourth-level liver surgery is an exceptionally demanding procedure, fraught with significant risks and technical complexities. Patients undergoing such operations face elevated surgical hazards, substantial physical trauma, prolonged recovery periods, and a multitude of factors that can profoundly impact their postoperative quality of life (QoL). Despite these challenges, there remains a notable gap in the literature regarding the long-term QoL outcomes for these individuals. This study seeks to evaluate the QoL of patients who have undergone fourth-level liver surgery and to identify key factors influencing their recovery. The findings aim to offer clinical insights that can enhance postoperative care and improve patient outcomes. Employing a prospective longitudinal cohort design, this study enrolled patients who received fourth-level liver surgery at a major tertiary hospital in Chengdu, affiliated with a university. QoL assessments were conducted using the EQ-5D-5L scale at three intervals post-discharge: one week, one month, and three months. This study enrolled 125 participants and tracked their health-related QoL using the EQ-5D-5L Utility Index (UI) (health utility values). Initially, 1 week post-discharge, most patients’ UI scores fell within the range of − 0.2 to 0.6. These values improved significantly over time, rising to 0.7–1.0 after 1 month and stabilizing between 0.8 and 1.0 by the 3 month mark. On average, patients reported experiencing pain for 4.18 days (± 9.72) following discharge. Statistical analyses—both univariate and multivariate—were performed to identify factors influencing QoL at different recovery stages. The findings revealed that admission method was a key determinant of QoL during the 1–3 month period post-discharge. Marital status emerged as a significant factor in the first week, while post-discharge pain levels primarily impacted QoL at the 1 month mark. After fourth-level liver surgery, the vast majority of patients regain their mobility, the ability to care for themselves, and their typical daily activities by 3 months post-discharge. Patients who are admitted to the emergency department tend to experience a lower QoL from 1 to 3 months following their discharge, compared to those who are admitted to the regular department. The persistent pain is a major culprit in diminishing a patient’s overall well-being. Consequently, prompt pain management and rehabilitation workouts are essential for expediting recovery and enhancing the patient’s QoL.